A survey of the history of global Christianity - Nickens, Mark (B & H Academic, 2020)
"Since Jesus's resurrection, Christianity has expanded across the globe and shaped a vast array of groups and movements. A Survey of the History of Global Christianity, Second Edition, provides an overview of the Christian faith from the apostolic age to the global present. In a friendly and informative tone, author Mark Nickens outlines the historical context of important developments in doctrine and practice, including:o the persecution and resilience of the early churcho the results of increasing papal power in Europe during the Middle Ageso the Reformation and later movements that influenced European Christianityo the various sects of American Christianity that arose in cycles of revivalo an examination of Orthodoxy and the history of Christianity in Asia, Africa, Latin America, and the West Indies. In addition to historical information, this book features quotes and spiritual lessons from noteworthy Christians throughout the centuries. By understanding how Christian doctrine has developed over the ages and across the globe, readers will better understand where their own faith tradition comes from."--